Exploring Alternative Neolithization Trajectories in Northeast China (Nen River Basin) - Tan, Yunchen; Piezonka, Henny; Jordan, Peter ; 0000-0002-2837-3920 (Quaternary International, 2025)
Understanding the drivers of diversity and change in regional Neolithization trajectories has emerged as a major theme in World Prehistory with new insights appearing in many parts of the globe. In Northeast Asia, research on Neolithic transition over the past two decades has focused primarily on millet and rice domestication and their role in the rise of farming, social complexity, and early Chinese civilization. However, not all regions followed this agricultural trajectory. Instead, several areas exhibit “alternative” pathways to sedentism, storage-based economies, and emergent social diversification, but these remain underrepresented in international literature. In Northeast China, the Nen River basin, located north of the early farming communities of the Yellow and Liao River basins, is one such region. The Nen River drains into the Songhua River, one of the major tributaries of the Amur River, which drains into the Pacific Ocean. Importantly, the Nen River basin includes extensive wetlands and rich mosaic environments, which emerged during climatic shifts during the Pleistocene-Holocene transition. These aquatic ecosystems supported a transition to broad-spectrum foraging, which in turn led to sedentism and emergent social complexity without any evidence of plant domestication or substantial reliance on staple crops. These sites flourished culturally and demographically under the ameliorating conditions of the Holocene Climatic Optimum, but underwent a transition to nomadic pastoralism after the 4.2 ka cold and aridity event, with many distinctive local cultural traditions persisting. In this paper, we present an integrated synthesis of currently available archaeological and palaeo-environmental records from the Nen River basin. The aim is to reconstruct the cultural and social developments that arose from humanenvironmental interactions from the Late Pleistocene into the middle and late Holocene in this vital region of Northeast Asia. Our research indicates that Neolithization here occurred independently of agriculture, supported instead by aquatic and terrestrial resources. We further highlight the global potential for studying diverse “Neolithicities” across different world regions, and conclude with a series of themes and questions that require further research and cross-cultural synthesis.
Keywords: Holocene; Neolithic; Northeast China; Nen river basin; Affluent hunter-Fisher-gatherers; Social diversification